Women and men diagnosed with acute coronary syndrome – sex-related differences - Magdalena Dudek; Marta Kałużna-Oleksy; Jacek Migaj; Ewa Straburzyńska-Migaj (Journal of Medical Science, 2018)
Background. Coronary artery disease (CAD) is one of the most important causes of death in both men and women. There are many gender differences among patients with CAD, including risk factors and acute coronary syndrome (ACS) outcomes. The latest reports showed that mortality due to CAD is higher in women than in men. Cardiac biomarkers play an important role in risk stratification and choice of treatment strategy in patients with ACS, however some of cardiac biomarkers show worse sensitivity and specificity in women. Aim. The aim was to investigate the sex-related differences in patients with acute coronary syndrome and to compare their sex-related risk of in-hospital mortality. Material and Methods. Single-center study of patients diagnosed with ACS who underwent precutaneous coronary intervention (PCI). Patients were diagnosed and treated according to ESC Guidelines. Statistical analysis was performed using StatSoft Statistica. Results. Of the 297 patients included in this study, 32% were women and 68% were men. There were 26.94% STEMI patients, 22.22% NSTEMI patients and 50.84% unstable angina patients. Compared with males, females were significant older (68.2 ± 10.6 vs. 64.8 ± 11.0; p = 0.0175). Levels of biomarkers of myocardial injury were significantly lower in women: CK-MB (p = 0.0241), troponin I (p = 0.0417) and CK (p = 0.0035) than in men. Women were less frequently treated with PCI or CABG (p = 0.0016) but the in-hospital outcomes (cardiogenic shock, sudden cardiac arrest or cardiac death) were similar in both groups (p = 0.8557). Conclusions. Women with ACS were older and have higher incidence of non-ST-elevation ACS than men.. In-hospital mortality show no significant difference between genders. Women were less likely to receive invasive treatment.